DAYA MINAT DALAM PENGGUNAAN BAHASA INGGRIS DAN PENGARUHNYA TERHADAP KOMUNIKASI MASYARAKAT INDONESIA - Putri Ananda, Eliza (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
In the era of globalization and advances in information technology, the use of foreign languages has become an increasingly common phenomenon in various countries. Foreign languages are often used in daily communication, mass media, the entertainment industry and the business sector. This phenomenon has sparked widespread debate about the social and cultural implications that arise as a result of the onslaught of foreign language use. In some cases, the use of foreign languages can threaten the sustainability of a country's indigenous language and culture. This has prompted efforts to defend local languages and cultures, as well as stirring feelings of nationalism. This phenomenon has sparked widespread debate about the social and cultural implications that arise as a result of the onslaught of foreign language use. In some cases, the use of foreign languages can threaten the sustainability of a country's indigenous language and culture. This has prompted efforts to defend local languages and cultures, while also stirring feelings of nationalism. The use of foreign languages is also used in the education system. Such use can bring benefits such as greater access to global resources and study abroad opportunities. However, there are also concerns that the excessive use of foreign languages may hinder students' ability to learn and master their mother tongue. In order to deal with the phenomenon of the onslaught of foreign language use, a balanced approach is needed between the needs of global communication and the interests of maintaining national culture and identity. Awareness of the social, cultural and economic implications of foreign language use needs to be raised so that people can make informed decisions in utilizing the potential of foreign languages while still strengthening their cultural identity and native language. Governments and educational institutions have an important role in regulating the use of foreign languages in community contexts. They need to consider the protection and maintenance of local languages and cultures, while still promoting the learning and understanding of relevant foreign languages